Media Constituents as a Differential Factor for Thermal Stress Susceptibility in Alternaria brassicicola Causing Dark Spot Disease of Brassica - Sinha, Diksha; Kushwaha, Chanda; Sarkhel, Subhashish (International Journal of Economic Plants, 2025)
The research was conducted during March, 2019 at Bihar Agricultural College, Sabour (Bhagalpur), India to study the effect of culture media and temperature on the mycelial growth and sporulation of fungal pathogen Alternaria brassicicola isolated from Indian mustard. The radial growth of the fungi and conidia concentrations (number of conidia ml-1 of suspension) were assessed on five culture media: potato dextrose agar (PDA), Czapek dox agar (CDA), Richard’s agar (RA), Asthana and Hawker’s agar (AHA) and Minimal media (MM) at three temperatures viz.; 15°C, 25°C and 35°C. The interaction of these two factors with growth parameters of the fungi was analysed to find alterations in growth patterns and spore production. Among the two factors examined, temperature most significantly influenced both radial growth and sporulation capacity of the pathogen. Among the five tested media, PDA was recorded as the most suitable for in vitro growth of A. brassicicola at 25°C (85.20 mm), while maximum mycelial growth (34.67 mm) at 35°C was recorded on CDA medium after 7 days of incubation. Cations like Fe+2 and Mg+2 were found to be beneficial in sustaining fungal growth at 35°C. Sporulation was best on RA media (14.47×104 spores ml-1) at 15°C. Mycelial growth was limited at 35°C (24.58 mm) followed by 15°C (30.10 mm) with optimum at 25°C. The results indicate that limiting magnesium and/or iron could inhibit growth of A. brassicicola under thermal stress.